A long-term perspective to the effects of the 2023 marine heat wave on stony corals in the Caribbean - Edmunds, Peter J; Lasker, Howard R (Biology letters (2005), 2025)
Marine heat waves (MHW) are a leading cause of death for stony corals, and it is reasonable to expect that a record-breaking MHW would negatively impact coral communities; 2023-2024 provided a test of this assertion in St John, US Virgin Islands, where an intense MHW brought temperatures of 30.6°C and degree-heating weeks of 23.23°C-weeks. On reefs where coral cover has been low for decades, the 2023/2024 MHW did not have discernable effects on coral cover. Nonetheless, there was a trend between 2023 and 2024 for mean coral cover to decline by small absolute (≤ 3%), but large relative (13-27%) amounts, with these changes affecting multiple genera and perturbing coral assemblages. These trends are eclipsed by the massive changes that have affected these coral communities since 1987; the 2023/2024 MHW was the latest in a series of disturbances transitioning these reefs to low coral cover. This MHW did not statistically depress coral cover, but it changed coral assemblages, intensifying the ecological perils of rarity, extirpation and perhaps local extinction.